Total Ionizing Dose Response of Different Length Devices in 0.13μm Partially Depleted Silicon-on-Insulator Technology - 张梦映 胡志远 张正选 樊双 戴丽华 刘小年 宋雷 (Chinese physics letters, 2017)
An anomalous total dose effect that the long length device is more susceptible to total ionizing dose than the short one is observed with the 0.13？μm partially depleted silicon-on-insulator technology. The measured results and 3D technology computer aided design simulations demonstrate that the devices with different channel lengths may exhibit an enhanced reverse short channel effect after radiation. It is ascribed to that the halo or pocket implants introduced in processes results in non-uniform channel doping profiles along the device length and trapped charges in the shallow trench isolation regions.